2018
DOI: 10.1055/a-0746-8698
|View full text |Cite
|
Sign up to set email alerts
|

Stellera chamaejasme and Its Main Compound Luteolin 7-O-Glucoside Alleviates Skin Lesions in Oxazolone- and 2,4-Dinitrochlorobenzene-Stimulated Murine Models of Atopic Dermatitis

Abstract: Stellera chamaejasme, also known as “Langdu”, has been traditionally used for the management of skin-related diseases such as psoriasis and skin ulcers. The aim of this study was to determine whether S. chamaejasme and its major component, luteolin 7-O-glucoside, have a preventive effect on the development of atopic dermatitis in oxazolone-treated BALB/c mice and 2,4-dinitrochlorobenzene-treated hairless mice. The epicutaneous applications of oxazolone and 2,4-dinitrochlorobenzene evoke an experimental murine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…In addition, the major active compound of the EtOH extract, luteolin 7-O-glucoside, decreased serum IgE and IL-4 levels, epidermal thickening as well as transepidermal water loss and increased skin hydration, therefore, showing strong anti-atopic dermatitis activity. 93 In addition, in the proliferative canine keratinocyte cell line CPEK, luteolin down modulated expression of IL-33, IL-1β, IL-6 and IL-8 after lipopolysaccharide (LPS) stimulation, indicating that luteolin might also enable the treatment of canine atopic dermatitis. 94 Interestingly, luteolin as the active component of Perilla frutescens L. (Lamiaceae) was also shown to inhibit the production of IL-4 in a house dust mite (HDM) induced murine Balb/c model of allergic rhinitis.…”
Section: Contact Dermatitis and Atopic Dermatitismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the major active compound of the EtOH extract, luteolin 7-O-glucoside, decreased serum IgE and IL-4 levels, epidermal thickening as well as transepidermal water loss and increased skin hydration, therefore, showing strong anti-atopic dermatitis activity. 93 In addition, in the proliferative canine keratinocyte cell line CPEK, luteolin down modulated expression of IL-33, IL-1β, IL-6 and IL-8 after lipopolysaccharide (LPS) stimulation, indicating that luteolin might also enable the treatment of canine atopic dermatitis. 94 Interestingly, luteolin as the active component of Perilla frutescens L. (Lamiaceae) was also shown to inhibit the production of IL-4 in a house dust mite (HDM) induced murine Balb/c model of allergic rhinitis.…”
Section: Contact Dermatitis and Atopic Dermatitismentioning
confidence: 99%
“…Regarding other forms of dermatitis, Jo et al have analyzed the effects of an ethanol extract of the aerial parts of Stellera chamaejasme L. (Thymelaeaceae) on oxazolone-or 2,4-dinitrochlorobenzene stimulated murine models of atopic dermatitis (AD). 93 Stellera chamaejasme contains diverse flavonoids and coumarins with anti-oxidative, anti-viral and anti-cancer activities as well as anti-inflammatory, analgesic and wound healing activities and exerted anti-atopic properties in the AD models. In addition, the major active compound of the EtOH extract, luteolin 7-O-glucoside, decreased serum IgE and IL-4 levels, epidermal thickening as well as transepidermal water loss and increased skin hydration, therefore, showing strong anti-atopic dermatitis activity.…”
Section: Contact Dermatitis and Atopic Dermatitismentioning
confidence: 99%
“…In addition, the efficacy of dupilumab, the drug that regulates IL-4, is known to be the best in the clinical trial. Previous papers have demonstrated that the extracts of natural products inhibiting IL-4 expression and some of the compounds isolated therefrom have excellent efficacy against atopic dermatitis in vivo [50,51] Therefore, compounds that inhibit IL-4 expression can be inferred to be able to ameliorate atopic dermatitis in vivo. Gallic acid and ellagic acid have previously been reported to have extensive anti-inflammatory activities, as revealed in our experiments.…”
Section: Isolation Of Phytochemicals From Ase and Their Effects In Rbmentioning
confidence: 99%
“…Inflamed cells were treated with the nutraceutical mixture containing luteolin, piceatannol, and cannabidiol at doses established through the literature and MTT assay results (22)(23)(24). The effects of the individual mixture components on the skin inflammation markers were already known in the literature so their synergic ability has been evaluated here (25)(26)(27). Piceatannol [dissolved in dimethyl sulfoxide (DMSO)] and luteolin and cannabidiol (dissolved in methanol) were added directly to the culture medium at the following concentrations (Mix 1: cannabidiol 10 µM, luteolin 10 µM, and piceatannol 10 µM; Mix 2: 10:25:25; Mix 3: 10:50:50; and Mix 4: 10:100:100 µM) for 4 h and 8 h. The culture medium containing vehicles alone was added to controls under the same conditions.…”
Section: Nutraceutical Dosage Information and Effects On Cell Viabilitymentioning
confidence: 99%